The Impact of Open Unemployment, Education, and Pad on Economic Growth and Employment Oportunities in the Bali Province Districts and Cities (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
Economic growth and increasing employment opportunities are important indicators for regional development, especially in Bali Province characteristics by tourism. Conditions in Bali Province show that growth has not automatically created employment opportunities evenly due to differences in dominant sectors between regions. The objective of this study: (1) examine the affect of open unemployment, education, and PAD on economic growth; (2) examine the impact of open unemployment, education, PAD, and economic growth on employment opportunities; and (3) determine the indirectly affect of open unemployment, education, and PAD on employment opportunities through economic growth in Bali Province’s districts/cities. A quantitative method is employed with a panel data regression path analysis approach, with data from 2017-2024 in nine districts/cities, 72 observations. The FEM is used. The findings indicate that (1) open unemployment has a negative and significant large impact on economic growth, education and PAD have a positive and significant effect on economic growth. (2) Employment opportunities are negatively and significantly impacted by open unemployment, not positively and significanly by education, positively and insignificanlt by PAD, and not positively and not significanly impacted by economic growth. So, (3) the affects of open unemployment, eduaction, and PAD on employment opportunities in Bali Provinces districts/cities are not mitigated by economic growth. In order to promote growth and equal job opportunities in Bali Province, our findings highlight strategies that lower unemployment, match education to labor market demands, and maximize PAD.